Penerapan Metode Pembelajaran Berbasis Proyek Dalam Pembelajaran IPA Di Sekolah Dasar - Handono, Dwi; Nisa, Ana Fitrotun; Prihatni, Yuli (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2023)
Natural Science learning in elementary schools has an important role in forming the basis of students' knowledge and interest in science. This research aims to describe the implementation of project-based learning in science learning in elementary schools. This description reveals information regarding the condition of students' interest in learning, the condition of students' understanding, and the condition of students' activeness when implementing science learning by implementing project-based learning. The research method used in this research is descriptive. Research data was obtained through observation and interviews. The data analysis technique applied uses 4 stages, namely data collection, data reduction, data display, ending with drawing conclusions. The research results show that the application of project-based learning methods in science learning in elementary schools can increase students' interest in learning, increase students' understanding of science concepts, and activate students in learning activities. The role of the teacher as a facilitator and motivator is very important in implementing project-based learning methods in science learning in elementary schools, so teachers of course need to continue to innovate and improve competence in carrying out teaching in the classroom.